Knowledge-Based Marketing Sebagai Solusi Peningkatan Daya Saing Usaha Kecil Menengah (UKM) Dengan Menggunakan Soft System Methodology - Haryati, Septi; Wardianto, Kussuyatmono Bagus; Saptiani, Fenny (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2024)
The purposes of this study were to describe the knowledge transfer process between banana chip SMEs in Bandarlampung as the recipient of knowledge with the government and large companies as knowledge providers, identify and analyze problems in the knowledge transfer process in the banana chip SME business in Bandarlampung and its impact on the ecosystem banana chip SME business in Bandarlampung, and produce the desired and feasible action suggestions to solve problems in the process of knowledge transfer in the banana chips SME business ecosystem in Bandarlampung. The type of research used was action research with a qualitative paradigm approach. The informants in this study came from Dinas Koperasi dan UKM in Lampung Province and Bandarlampung, PTPN VII Bandarlampung, and banana chips SMEs entrepreneurs in Bandarlampung. Data collection techniques applied in this research were observations, literature study, in-depth interviews and documentations. The data analysis used was the data analysis stage technique which was adapted from the Soft Systems Methodology approach. The data validity technique was applied using the recoverability method. The results of this study indicated that the government and large companies had been providing a knowledge based on Knowledge-Based Marketing with lecture and vocational methods for the implementation of SME development and coaching programs. Systemic problems arose in the learning process of banana chips SMEs entrepreneurs in Bandarlampung that are not yet optimal, creating a business behavior that tends to be stagnant even though they have received an SMEs development and coaching program.